Komi can't communicate. Volume 10 - Oda, Tomohito, 1991-; Werry, John (Translator) (Shōnen Sandē komikkusu., 2020)
"Komi is starting her second year of high school, and she's feeling a bit melancholy that all the good times of the previous year are now behind her. How can anything else compare? But when Komi runs into a girl in her new class with outrageous fashion sense crying in the bathroom, she's able to put all her wonderful friend-making experience to good use and reach out to another person in need."--Provided by publisher.